Tinjauan Yuridis Pendistribusian Zakat Beasiswa menurut UU dan Peraturan BAZNAS - Fina Ifadatus Silmi; Hendra Kholid (JURNAL ILMIAH NUSANTARA, 2026)
Zakat plays a strategic role in realizing social justice and improving community welfare. This study aims to analyze the distribution mechanism of zakat funds through the Jakarta Future Scholarship (Masa Depan Jakarta/MDJ) Program organized by BAZNAS (BAZIS) DKI Jakarta, with reference to Law No. 23 of 2011 and BAZNAS Regulation No. 1 of 2023. This research employs a qualitative method with a juridical approach and case study design. Primary data were obtained through interviews, while secondary data were collected from literature, journals, and relevant regulations. The findings indicate that zakat distribution through the MDJ program has been implemented in a transparent and accountable manner, involving rigorous selection, online registration, and direct fund transfers to recipients. The implementation is consistent with Law No. 23 of 2011 Articles 25–27 and BAZNAS Regulation No. 1 of 2023, particularly regarding transparency, accountability, accuracy, and sustainability principles.